2020
DOI: 10.3389/fvets.2020.00471
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Health Indicators to Assess Cull Cow's Welfare in Livestock Markets

Abstract: The welfare status of cull cows going through livestock markets was assessed in 12 premises in Chile, using behavioral and health indicators observed during unloading, auction, and loading (once in winter and once in summer). Groups of cows were observed by the same observer and the following indicators were recorded at each stage: slips, falls, balks, turns, jumps, and vocalizations of cows were considered as behavioral events and a proportion was calculated based on the number of observed events per group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…During unloading of the calves, we found that slips (25.1%), followed by vocalizations (14.7%), were the most frequently observed, whereas slips (14.7%) and reversals (11.5%) were the most frequently observed during loading. Observations performed in cull cows during unloading and loading in the same auction markets showed similar results [34]. However, in both cases, the percentages of these behaviours were much higher than acceptable according to Grandin [33].…”
Section: Welfare Indicators During Unloading and Loading Proceduressupporting
confidence: 56%
“…During unloading of the calves, we found that slips (25.1%), followed by vocalizations (14.7%), were the most frequently observed, whereas slips (14.7%) and reversals (11.5%) were the most frequently observed during loading. Observations performed in cull cows during unloading and loading in the same auction markets showed similar results [34]. However, in both cases, the percentages of these behaviours were much higher than acceptable according to Grandin [33].…”
Section: Welfare Indicators During Unloading and Loading Proceduressupporting
confidence: 56%
“…Cull cows may be sent for slaughter via auction markets. Sending cull animals to an auction market often will involve consecutive journeys, increase the overall journey duration and expose the animals to extra handling (Sánchez‐Hidalgo et al., 2020), novel environments, restricted availability of feed and water, cold or hot environments; provide reduced opportunities for rest; and more opportunity for any existing health condition to deteriorate. If the marketing process is prolonged, it can result in a loss of body weight (Arp et al., 2011), body condition (Stojkov et al., 2020) and signs of dehydration (Vogels et al., 2011).…”
Section: Assessmentmentioning
confidence: 99%
“…Bruises result from damaged blood vessels due to a blow on the skin, and scratches are surface wounds. They may be caused by the use of sticks, collisions with equipment or other animals, or by a vertical sliding door closed while an animal is underneath, striking its back or shoulders (Bourguet et al, 2011a;Sanchez-Hidalgo et al, 2020;Strappini et al, 2013). Lacerations and tears penetrate the skin and are caused by sharp objects, such as hoofs and teeth of conspecifics, or sharp pen fittings.…”
Section: Consequences Of Stress Reactions On Carcass and Meat Quality...mentioning
confidence: 99%